Very low inadequate dietary intakes of essential n-3 polyunsaturated fatty acids (PUFA) in pregnant and lactating French women: The INCA2 survey. (January 2019) - Tressou, Jessica; Buaud, Benjamin; Simon, Noëmie; Pasteau, Stéphane; Guesnet, Philippe
Highlights: The majority of the French population of pregnant and lactating women ingested insufficient amounts of both long-chain n-3 PUFA and alpha-linolenic acid (ALA). Daily intakes of n-3 PUFA in some pregnant and lactating women were 4 times (ALA) to 10 times (docosahexaenoic acid, DHA) lower than the recommended dietary intakes (RDIs). Similar intakes were also noted in women of childbearing age, suggesting that pregnant and lactating women did not change their dietary habits to favor ALA and n-3 long-chain PUFA consumption via the consumption of rich-ALA vegetable oils and fish and oily fish, respectively. Summary: Background: The French National survey INCA2 pointed out that the majority of the French population (children, adolescents, adults and elderly) ingest low quantities of n-3 polyunsaturated fatty acid (PUFA) in the form of both precursor (alpha-linolenic acid, ALA) and long-chain (mainly docosahexaenoic acid, DHA). However, we don't know whether such inadequate n-3 PUFA consumption is also found again in pregnant and lactating women. Methods: Dietary lipid and PUFA intakes were determined from 28 pregnant and 21 lactating French women by using the most recent set of national robust data on food (National Survey INCA2 performed in 2006 and 2007), and compared with that of 742 women of childbearing age. Results: Main results showed that mean daily intakes of n-3 PUFA were very low in this French woman population because no pregnant and lactating women met recommended dietary intakes (RDIs). Moreover, some of them ingested quantities 4 times (ALA) to 10 times (DHA) lower than RDIs. Very similar dietary intakes were observed in women of childbearing age. Conclusion: French pregnant and lactating women did not change their dietary habits to favor ALA and n-3 long-chain PUFA consumption via rich-ALA vegetable oils and fish and oily fish consumption, and have low n-3 PUFA dietary consumption typical of French women of childbearing age. Such PUFA intakes could have adverse impact on long-chain n-3 PUFA incorporation in brain membranes of fetus and infants, but also on cognitive and visual development of infants during the first years of life.